Syk facilitates phagosome-lysosome fusion by regulating actin-remodeling in complement-mediated phagocytosis - Hiroyuki Tabata (Nature Portfolio, 2020)
Abstract Effective phagocytosis is crucial for host defense against pathogens. Macrophages entrap pathogens into a phagosome and subsequently acidic lysosomes fuse to the phagosome. Previous studies showed the pivotal role of actin-remodeling mediated by phosphoinositide-related signaling in phagosome formation, but the mechanisms of phagosome-lysosome fusion remain unexplored. Here we show that in complement-mediated phagocytosis, phagosome-lysosome fusion requires the disappearance of F-actin structure surrounding the phagosome and a tyrosine kinase Syk plays a key role in this process. Using macrophage-like differentiated HL60 and Syk-knockout (Syk-KO) HL60 cells, we found that Syk-KO cells showed insufficient phagosome acidification caused by impaired fusion with lysosomes and permitted the survival of Candida albicans in complement-mediated phagocytosis. Phagosome tracking analysis showed that during phagosome internalization process, F-actin surrounding phagosomes disappeared in both parental and Syk-KO cells but this structure was reconstructed immediately only in Syk-KO cells. In addition, F-actin-stabilizing agent induced a similar impairment of phagosome-lysosome fusion. Collectively, Syk-derived signaling facilitates phagosome-lysosome fusion by regulating actin-remodeling.